Climate Change in Nepal’s Context: A Looming Crisis Demanding Urgent Action - Dangal, Dipak Kumar (Creative Vision: Multidisciplinary Journal of PMC, 2025)
Nepal, renowned for its breathtaking landscapes and diverse ecosystems, is increasingly vulnerable to the escalating threats posed by climate change. This crisis is requiring urgent action. The numerous and severe effects of climate change on Nepal’s environment, economy, and communities are examined in this article. Accelerated glacial melt, erratic and unpredictability in monsoon patterns, increased agricultural instability, and the destruction of essential habitats for wildlife are major causes for concern. The underlying scientific causes of these changes and their significant impact on local ecosystems, human livelihoods, and national development are the subject of the study. Nepal’s reliance on environment delicate areas, for example, farming and the travel industry make it especially helpless with these impacts. The need for both top-down policy interventions and grassroots initiatives is also emphasized in the article’s review of global and national efforts to mitigate climate change. It emphasizes the crucial role that individuals and communities can play in climate adaptation and mitigation strategies and calls for urgent collective action. With Nepal’s future in danger, shielding its ecological strength is fundamental for guaranteeing the prosperity of its kin and saving its exceptional normal legacy. In order to address the growing climate crisis before its effects become irreversible, this comprehensive study aims to raise awareness and inspire proactive measures.